Dampak Psikologis Kekerasan dalam Rumah Tangga pada Anak Usia Dini - Gita Permata Sari (Lembag, 2024)
The family is a fundamental environment for the growth and development of children, where parental affection and protection are essential to ensure the physical and mental health of children. However, in reality, many children experience disturbances in their growth, one of which is due to domestic violence (KDRT), which often occurs in an environment that should be safe for children. KDRT has the potential to create psychological trauma both directly and indirectly for children, which can interfere with their social and emotional development. Data from the National Commission on Violence Against Women shows the high number of cases of domestic violence in Indonesia, with a significant proportion of victims being children. This article aims to examine the psychological impact experienced by children when witnessing family conflict, with a focus on the mental health and behavioral aspects of children. Through a concrete case analysis, such as the experience of an influencer who experienced domestic violence, this article highlights the urgency of the problem and the long-term psychological impact of domestic conflict. With a deep understanding of these effects, this article is expected to provide recommendations for parents, educators, and authorities to minimize the psychological risks faced by children in situations of domestic conflict.